Plankton and Macrozoobenthos as Bioindicators of Water Quality in the Gendol River, Yogyakarta - Idris, Muhammad Arsya; Langsa, Pelangi Karen; Treeza, Yoanita Amanda; Nabila, Faisa Nisrina Zakiyatun; Panggabean, Christina Romauli; Andini, Novia Fitri; Handziko, Rio Christy; Mualimin, Mualimin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Gendol River, originating from the slopes of Mount Merapi, is one of the main freshwater sources in Yogyakarta and is increasingly affected by anthropogenic activities that may alter its water quality. This study aimed to assess the water quality of the Gendol River using an integrated analysis of physical, chemical, and biological parameters, with plankton and macrozoobenthos communities serving as bioindicators. Sampling was conducted at three stations representing upstream, midstream, and downstream sections using standard limnological methods. Physical and chemical parameters included temperature, turbidity, pH, dissolved oxygen, biochemical oxygen demand, and salinity, while biological parameters focused on the identification of plankton and macrozoobenthos. The results indicated a longitudinal decline in water quality from upstream to downstream, characterized by increasing organic load, reduced water clarity, and decreasing biological diversity. Changes in plankton composition and the dominance of tolerant macrozoobenthos taxa reflected varying levels of environmental disturbance along the river. These findings confirm that plankton and macrozoobenthos are effective bioindicators for evaluating ecological conditions in tropical freshwater systems and highlight the need for improved river management strategies, particularly in controlling anthropogenic pressures to maintain the ecological sustainability of the Gendol River.